Influence Analysis and Spectral Shape Correction of Nuclear Magnetic Logging in Ultra-Deep Oil and Gas Wells - CHEN Guojun; ZHANG Xiao; GAO Ming; ZHANG Fan; ZHANG Jin; FAN Xiaoqin (Cejing jishu)
The ultra-deep wells in Junggar basin are drilled with oil-based mud. The oil-based mud intruded into the formation affects the physical response characteristics of nuclear magnetic logging, and can not truly reflect the pore structure of the formation. Through the high temperature core nuclear magnetic resonance experiment, it is found that the bound peak decreases and the movable peak increases after the invasion of oil-based mud, but the total pore changes little before and after the invasion. Through the experimental parameters, the reservoir is divided into three types to establish a correction model. The application results show that the corrected T2 spectrum can more truly reflect the pore structure characteristics, and the average relative error of the mobile porosity before calculation is reduced from 25% to 7% compared with the mobile porosity after calculation, effectively improving the interpretation accuracy of the mobile porosity. This study provides logging technology support for the next exploration deployment in the southern margin of the Junggar basin.